Sociodemographic factors influencing environmental perception and local ecological knowledge in forests of different ages in Northeastern Brazil - Ribeiro dos Santos, Francisco Igor; Lacerda e Medeiros , Maria Jaislanny; Morais, Rodrigo Ferreira; Gomes Reis Lopes, Clarissa (Ethnobotany Research and Applications, 2023)
Background: Local ecological knowledge (LEK) has been a great ally in developing conservation strategies that are more attuned to the local reality. However, since this knowledge is dynamic, it is necessary to conduct studies that understand how cultural, sociodemographic and ecological factors can affect it. In this regard, the present study to assess the knowledge of farmers from different communities regarding plant species in forests of varying ages, as well as the sociodemographic and environmental perception factors that may influence them. Methods: The study was conducted in two rural communities in the municipality of José de Freitas, Piauí, Brazil. The research involved farmers who possess knowledge about forests of different ages, selected through the snowball sampling technique. Data were collected through semi-structured interviews and guided tours for species collection. A total of 36 farmers participated in the study, including nine women and 27 men. Results: : Our study unveiled distinct plant species knowledge in rural communities for forests of varying ages, often tied to cultural contexts. Sociodemographic and environmental factors analysis revealed age and perceived forest regeneration time influenced early-stage plant knowledge. For late-stage plant knowledge, factors included fragment visits, perception of regeneration time, and their interaction. While communities had differing knowledge on early and late-stage plants, common explanatory factors emerged. Conclusions: The study suggests that in the studied communities, it’s important to consider both age and current environmental experiences of farmers in LEK studies. This highlights the valuable contributions of both older and younger farmers in understanding changes in forest fragments of varying ages. Keywords: Ethnobotany, dynamics of ecological knowledge, biodiversity conservation, natural regeneration.